Inhibin/activin-betaC subunit in human endometrial adenocarcinomas and HEC-1a adenocarcinoma cell line - Käufl, Stephanie D.; Makovitzky, József; Kuhn, Christina; Kunze, Susanne; Jeschke, Udo; Mylonas, Ioannis (In vivo, 2010)
Introduction: Inhibins and activins are important regulators of the female reproductive system. Recently, two novel inhibin subunits, named betaC (βC) and betaE (βE), have been identified. However, only limited data on the expression of the βC subunit in human endometrioid adenocarcinomas exist. Materials and Methods: Samples of uterine endometrioid adenocarcinomas were obtained and analysed by immunohistochemistry for the immunolabelling with an inhibin-βC antibody. Additionally, the endometrial cancer cell line HEC-1a was used to assess the inhibin-betaC expression with the use of immunofluorescence. Results: Expression of the inhibin-βC subunit was demonstrated at the protein level by means of immunohistochemical evaluation in human endometrioid adenocarcinomas and the HEC-1a cell line. Discussion: This study demonstrated, for the first time, that the novel inhibin/activin-βC subunit is expressed in human endometrioid adenocarcinomas and in the human endometrial carcinoma cell line HEC-1a. Whether this novel β-subunit has a substantial role in the pathogenesis and malignant transformation in human endometrium is still under investigation.